Praktik Wanita Pekerja Seks (WPS) Dalam Pencegahan Penyakit Infeksi Menular Seksual (IMS) Dan HIV&AIDS Di Lokalisasi Koplak, Kabupaten Grobogan - Widodo, Edy (Jurnal Promosi Kesehatan Indonesia, 2009)
Background: STI cases in Grobogan were increase, from 27 cases in 2007 to 58 cases in 2008, with fatality rate around 20%. At Koplak brothel, syphilis prevalence among female sex workers reached 18% whilst HIV prevalence remains lower at 6.5%. This research aims to analyze factors associated to female sex workers’ STI and HIV-AIDS prevention practice.Method: This study was an explanatory research employed cross sectional approach combining quantitative and qualitative methods. There were 70 females sex workers were involved in quantitative study whilst 7 other respondents were involved in qualitative study. Univariate analysis and Fisher Exact Test were employed to analyze quantitative data whilst content anaysis was used to analyze qualitative data.Result: It was found perceived benefits of prevention and perceived self efficacy were correlated to female sex workers’ prevention practice whilst perceived susceptibility and cues to action were not statistically significant. In order to improve female sex workers’ knowledge on STI and HIV-AIDS prevention, it is necessary for local government to address female sex workers’ perceived susceptibility by adopting testimonials methods and involving peer groupswho have safer sex behavior.Keywords : Prevention, Practice, Female, Sex, Worker, Perception, STI